Belief Revision towards Long-Series Information - Tri Ika Ayuananda; Intiyas Utami (Journal of Economics, Business, and Accountancy Ventura, 2017)
The purpose of the research is to assess the primacy effect of the sequence for the manner of presentation and information formation on the audit decisions in revising the belief when the information is presented differently. The primacy effect is the decision by the auditor when the information is provided in sequence and weighting the larger initial information towards the auditor belief. This research used a 2x2x2 experimental design with 116 participants of the Undergraduate accounting majors (S1). The results of the research showed that: 1) the primacy effect on decision-making occurred when information was presented sequential pattern;2) the decision making audit, the primacy effects occurred Â in a visual form; 3) there is a primacy effect when the information is presented with a long series order.